Mario Vargas Llosa´s Elogio de la madrastra, total work of art, limits and proximities (2011)
This text intends to show historical and theoretical problems implied in the composition of the pictorial and erotic novel In praise of the stepmother, by the Peruvian Mario Vargas Llosa. The analytic reading of this verbal and visual work is faced up to